Explaining the Impacts of the “Performance Model of Donation” on “Reducing Sorrow and Fear” According to the Islamic Sources - Mohammad Kaviyani Arani; Amir Ekbia (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2022)
The current study aimed to explain the impacts of the “performance model of donation” on the reduction of “fear” and “sorrow” according to Islamic sources. The study tried to answer “what performance model allows donation to reduce fear and sorrow in human beings?” The above question was investigated among the Quranic verses and hadiths based on the theory of “semantic field”; thus, the Quranic verses and hadiths related to donation, alms, stinginess, miserliness, and generosity were investigated. The class analysis was applied to understand the components psychologically. The obtained components were classified in groups titled “orientations”, “behaviors”, “experiences”, and “functions”. Investigating the components in the above classes revealed that the lack of sorrow and fear is an internal experience and is not in complete agreement with external objectivities. If a donation is performed according to the Quranic approach and is in line with the above four classes of components, it will bring about certain “psychological functions” and “developmental impacts”; one of such “psychological functions” is “the reduction of sorrow” and “the reduction of fear” in the donator.